The role of the exchange rate for adjustment in boom and bust episodes - Reiner Martin; Ludger Schuknecht; Isabel Vansteenkiste (European Central Bank (ECB), 2007)
Numerous countries have experienced boom-bust episodes in asset prices in the past 20 years. This study looks at stylised facts and conducts statistical and econometric analysis for such episodes, distinguishing between industrialised countries that experienced external adjustment (via real effective exchange rate depreciation during busts) and those that relied on an internal adjustment process (and experienced no depreciation). The study finds that different adjustment experiences are correlated with the degree of macroeconomic imbalances and balance sheet problems. Internal adjustment seems more prevalent when financial vulnerabilities, excess demand and competitiveness loss remain relatively contained in the boom. In the bust, internal adjusters experience more protracted but less deep downturns than external adjusters as imbalances unwind more slowly. Some Central and East European EU Member States are currently experiencing strong credit and asset price growth in conjunction with rapid economic expansion. Against this background the experience of other countries may raise awareness of related policy challenges.
Keywords: E32; E63; E65; 330; Booms and busts; competitiveness; Exchange Rates; external and internal adjustment; financial imbalances; Konjunktur; Wechselkurspolitik; Strukturpolitik; Internationaler Wettbewerb; Industrieländer; EU-Mitgliedschaft